Dispute on Termination of Employment as a Impact of Company Mergers and Closures - Hermawan, Endang; Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to examine industrial relations disputes, especially employment termination disputes that occur as a result of mergers, consolidations, takeovers or company closures. This research method is legal research with a conceptual approach and a case approach. Collecting materials through literature study methods, with primary and secondary legal materials. Next, the legal materials are studied and analyzed using the approaches used in this research to answer the legal issues in this research. The results of this research show: The Employment Law is a legal product that was formed to protect workers. Legal protection for workers who experience termination of employment due to mergers, consolidations and takeovers of companies is regulated in the provisions of Article 163 of Law of the Republic of Indonesia Number 13 of 2003 concerning Employment, then regarding termination of employment due to company closure, legal protection for workers is regulated in the provisions of Article 164 of Law of the Republic of Indonesia Number 13 of 2003 concerning Employment. Termination of employment relations that occurs to workers due to mergers, consolidations, takeovers or company closures can give rise to industrial relations disputes, namely employment termination disputes.